2007
DOI: 10.1117/12.736071
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the potential for the use of a high resolution adaptive coded aperture system in the mid-wave infrared

Abstract: Previous applications of coded aperture imaging (CAI) have been mainly in the energetic parts of the electro-magnetic spectrum, such as gamma ray astronomy, where few viable imaging alternatives exist. In addition, resolution requirements have typically been low (~ mrad). This paper investigates the prospects for and advantages of using CAI at longer wavelengths (visible, infrared) and at higher resolutions, and also considers the benefits of adaptive CAI techniques. The latter enable CAI to achieve reconfigur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…As both metmaterials and liquid crystals have been shown to operate across much of the electromagnetic spectrum this would enable an innovative substitute for digital micromirror devices (DMDs), which are spectrally featureless and have set frequency limits [34]. Modern imaging research that could benefit from SLMs, such as compressive sensing [35], Hadamard imaging [36] and adaptive coded aperture imaging [37], would then be enabled at EM bands where conventional DMDs do not operate. The fabrication of focal plane arrays consisting of the designs demonstrated here could serve as an excellent candidate for detector pixels when implemented into bolometric, rectification, pyroelectric and piezoelectric configurations.…”
mentioning
confidence: 99%
“…As both metmaterials and liquid crystals have been shown to operate across much of the electromagnetic spectrum this would enable an innovative substitute for digital micromirror devices (DMDs), which are spectrally featureless and have set frequency limits [34]. Modern imaging research that could benefit from SLMs, such as compressive sensing [35], Hadamard imaging [36] and adaptive coded aperture imaging [37], would then be enabled at EM bands where conventional DMDs do not operate. The fabrication of focal plane arrays consisting of the designs demonstrated here could serve as an excellent candidate for detector pixels when implemented into bolometric, rectification, pyroelectric and piezoelectric configurations.…”
mentioning
confidence: 99%
“…By varying the aperture pattern, other benefits can be realized, which open the pathway for improved imaging quality, variable field of view and steerable field of regard [24]. In a sense, some of these follow-on from the initial suggestion of Grindley and Hong [20], who found that up to two orders of magnitude improvement in signal to background ratio could be obtained in X-ray imaging by scanning the field of view over the telescope.…”
Section: Figure 1 Schematic Diagram Highlighting Propagation Of Radiamentioning
confidence: 96%
“…Diffraction effects were analyzed at the beginning of their system design stage. The diffraction leads to energy dispersion of the information, which means there is a tradeoff between the convenience of measurement with more sensing cells and the algorithmic complexity for imaging reconstruction with high quality [15]. Their following works were mainly focused on PSF control (including mask pattern design [16] and microshutter array technology [17]) and the imaging reconstruction based on PSF calibration [18,19].…”
Section: Introductionmentioning
confidence: 99%